Strong functional stability of soil microbial communities under semiarid Mediterranean conditions and subjected to long-term shifts in baseline precipitation - Curiel Yuste, J; Fernandez-Gonzalez, a.J. J; Fernandez-Lopez, M; Ogaya, R; Penuelas, J; Sardans, J; Lloret, F (Soil Biology and Biochemistry, 2014)
Abstract We investigated the effect of soil microclimate on the structure and functioning of soil microbial communities in a Mediterranean Holm-oak forest subjected to 10 years of partial rain exclusion manipulations, simulating average drought conditions expected in Mediterranean areas for the following decades. We applied a high throughput DNA pyrosequencing technique coupled to parallel measurements of microbial respiration (RH) and temperature sensitivity of microbial respiration (Q10). Some consistent changes in the structure of bacterial communities suggest a slow process of community shifts parallel to the trend towards oligotrophy in response to long-term droughts. However, the structure of bacterial communities was mainly determined by short-term environmental fluctuations associated with sampling date (winter, spring and summer) rather than long-term (10 years) shifts in baseline precipitation. Moreover, long-term drought did not exert any chronic effect on the functioning of soil microbial communities (RH and Q10), emphasizing the functional stability of these communities to this long-term but mild shifts in water availability. We hypothesize that the particular conditions of the Mediterranean climate with strong seasonal shifts in both temperature and soil water availability but also characterized by very extreme environmental conditions during summer, was acting as a strong force in community assembling, selecting phenotypes adapted to the semiarid conditions characterizing Mediterranean ecosystems. Relations of climate with the phylogenetic structure and overall diversity of the communities as well as the distribution of the individual responses of different lineages (genera) to climate confirmed our hypotheses, evidencing communities dominated by thermotolerant and drought-tolerant phenotypes.
Keywords: Adaptation; CO2; diversity; Extreme events; functional stability; Mediterranean climate; Soil bacterial communities

Relationship between projected changes in future climatic suitability and demographic and functional traits of forest tree species in Spain - Lloret, F; Martínez-Vilalta, J; Serra-Diaz, J M; Ninyerola, M (Climatic Change, 2013)
The response of plant species to future climate conditions is probably dependent on their ecological characteristics, including climatic niche, demographic rates and functional traits. Using forest inventory data from 27 dominant woody species in Spanish forests, we explore the relationships between species characteristics and projected changes in their average climatic suitability (occurrence of suitable climatic conditions for a species in a given territory) obtained by empirical niche-based models, under a business-as-usual climate change scenario (A1, HadCM3, 2001–2100). We hypothesize that most species will suffer a decline in climatic suitability, with a less severe for species (i) currently living in more arid climates or exhibiting a broader current climatic niche; (ii) with higher current growth rates; (iii) with functional traits related to resistance to water deficits. The analysis confirm our hypothesis since apart from a few Mediterranean species, most species decrease their climatic suitability in the region under future climate, characterized by increased aridity. Also, species living in warmer locations or under a wider range of climatic conditions tend to experience less decrease in climatic suitability. As hypothesized, a positive relationship was detected between current relative growth rates and increase in future climatic suitability. Nevertheless, current tree mortality did not correlate with changes in future climatic suitability. In contrast with our hypothesis, functional traits did not show a clear relationship with changes in climate suitability; instead species often presented idiosyncratic responses that, in some cases, could reflect past management. These results suggest that the extrapolation of species performance to future climatic scenarios based on current patterns of dominance is constrained by factors other than species autoecology, particularly human activity.
APS
Keywords: climatic niche; demographic rates; funtional traits; future climate; Spain; woody species

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R; Lloret, F; Pons, X (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration